2011
DOI: 10.2500/ajra.2011.25.3676
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C in Revision Endoscopic Dacryocystorhinostomy: A Prospective Randomized Study

Abstract: The results of our study indicate that the application of intraoperative mitomycin C may improve the outcome in revision EN-DCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…One study was divided into two comparative groups as it included both primary and revision DCRs. Three studies were done in India [12], [13], [33], 3 in Turkey [11], [30], [32], and 1 each in Iran [15], Finland [34], Egpty [35], Thailand [14], and China [10]. The mean age of patients in most of studies ranged from 32 to 70 years and the percentage of female patients ranged from 42% to 90%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was divided into two comparative groups as it included both primary and revision DCRs. Three studies were done in India [12], [13], [33], 3 in Turkey [11], [30], [32], and 1 each in Iran [15], Finland [34], Egpty [35], Thailand [14], and China [10]. The mean age of patients in most of studies ranged from 32 to 70 years and the percentage of female patients ranged from 42% to 90%.…”
Section: Resultsmentioning
confidence: 99%
“…In 5 of all the RCTs included in the systematic review, the investigators described a random component in the sequence generation process such as: referring to a random number table [13] or using a computer random number generator [11], [34] or using a random blocks [14], [35]. The remainder did not describe the specific methods of random sequence generation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used, at the end of the revision procedure, a piece of tampon soaked in mmc (0.4 mg/mL) which was placed into the rhinostoma for 5 minutes. Therefore the authors suggested the application of intraoperative mmc to improve the outcome in revision endoscopic dacryocystorhinostomy [19]. Vascularity plays a big role in healing.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported very promising results. [12][13][14][15] But other studies have shown that use of mitomycin C at the operative site did not improve success rate significantly. [13] We used a topical 0.…”
Section: Introductionmentioning
confidence: 99%